1990
DOI: 10.1152/ajprenal.1990.259.3.f432
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus restriction reverses hyperparathyroidism in uremia independent of changes in calcium and calcitriol

Abstract: Phosphorus is a well-known modulator of renal 1 alpha-hydroxylase activity. In early and moderate renal failure it is proposed that dietary Pi reduction ameliorates secondary hyperparathyroidism through increased circulating levels of calcitriol (i.e, 1 alpha, 25-dihydroxycholecalciferol). To gain further insight into the mechanisms by which a low-Pi diet ameliorates secondary hyperparathyroidism in advanced renal insufficiency, studies were performed in five dogs before and 6 mo after the induction of uremia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
3

Year Published

1995
1995
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 22 publications
1
76
0
3
Order By: Relevance
“…In all these clinical situations the stimulus was hypocalcemia but hyperphosphatemia may have an independent role. Serum phosphate is invariably raised in chronic renal failure and correction of serum phosphate alone with no changes in serum calcium or 1,25(OH)2D3 corrects secondary hyperparathyroidism (39)(40)(41) and it is possible but not proven that phosphate may have a direct effect on the PT cell similar to that of calcium (3). In patients with intestinal malabsorption both the serum calcium and 1,25 (OH)2D3 levels would be decreased.…”
Section: Discussionmentioning
confidence: 99%
“…In all these clinical situations the stimulus was hypocalcemia but hyperphosphatemia may have an independent role. Serum phosphate is invariably raised in chronic renal failure and correction of serum phosphate alone with no changes in serum calcium or 1,25(OH)2D3 corrects secondary hyperparathyroidism (39)(40)(41) and it is possible but not proven that phosphate may have a direct effect on the PT cell similar to that of calcium (3). In patients with intestinal malabsorption both the serum calcium and 1,25 (OH)2D3 levels would be decreased.…”
Section: Discussionmentioning
confidence: 99%
“…However, this mechanism may not be operative in advanced renal insufficiency because the decrease in renal mass may limit the production of 1,25-(OH) 2 D 3 (3)(4)(5). Lopez-Hilker and collaborators (6) demonstrated in dogs with advanced renal insufficiency and severe secondary hyperparathyroidism that a gradual reduction of phosphorus in the diet was accompanied by a significant decrease in the levels of PTH without changes in ICa or 1,25-(OH) 2 D 3 . Although these data clearly demonstrated that the effect of phosphorus on PTH secretion was independent of changes in serum ICa and 1,25-(OH) 2 D 3 , they did not evaluate the role of phosphorus on parathyroid cell growth or establish if phosphorus directly affected the synthesis or secretion of PTH.…”
Section: Introductionmentioning
confidence: 99%
“…Ее клиническими по-следствиями являются ренальная остеодистрофия и прогрессирование вторичного гиперпаратиреоза [30,31], кальцификация мягких тканей и сосудов. Последняя четко связана с сердечно-сосудистой патологией [32,33].…”
Section: контроль гиперфосфатемииunclassified